Penerapan Akuntansi Zakat Infak Sedekah Produktif oleh LAZ Inisiatif Zakat Indonesia Kota Medan - Amalia, Nur; Harmain, Hendra; Harahap, Muhammad Ikhsan (LPPM Universitas Labuhanbatu, 2023)
This research was conducted at the Medan City branch of the Indonesian Zakat Initiative Amil Zakat Institute. This study aims to determine the implementation of PSAK 109 at IZI Medan branch. PSAK 109 explains that zakat is assets that must be issued by people who are obliged to pay zakat (muzakki) in accordance with sharia provisions to those who are entitled to receive it (mustahik). Likewise with infak/alms issued by muzakki in an effort to realize God's commands by helping human beings who are entitled to receive them and also helping the public good. The type of research conducted in this study is a type of qualitative research with a descriptive approach. The data collection method in this study is through; direct observation, interviews, documentation, reporting at IZI and then compared with the Statement of Financial Accounting Standards (PSAK). The results of this study indicate that the management of productive-based zakat infaq alms is good in receiving funds from muzakki and distribution to mustahik, and in financial reporting LAZNAS IZI Medan Branch has implemented PSAK 109 well in terms of recording and measurement while presentation and disclosure can only be made in reports finance at IZI central Jakarta only.